2022
DOI: 10.1039/d1qi01555a
|View full text |Cite
|
Sign up to set email alerts
|

A highly stable Zn9-pyrazolate metal–organic framework with metallosalen ligands as a carbon dioxide cycloaddition catalyst

Abstract: A three-dimensional (3D) metal-organic framework constructed from unprecedented Zn9O2(OH)2(pyz)12 (pyz = pyrazolate) clusters and Ni(salen)-derived linkers was reported. The MOF exhibits high catalytic activity for CO2 cycloaddition reactions with excellent...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 67 publications
2
13
0
Order By: Relevance
“…4. 67–71 Firstly, the cycloaddition reaction began with the O atom of epoxide being activated by the Lewis acidic In 3+ and Tm 3+ sites to form In/Tm-epoxide adducts, resulting in the instability of the ternary rings. Subsequently, the Br − ions released from the co-catalyst of n -Bu 4 NBr launched an affinity attack on the C atom with less steric hindrance to produce the main intermediates of alkylcarbonate anions, whose O − atoms served as a nucleophilic reagent to react with CO 2 in the pores, generating the carbonate ester as the secondary intermediate.…”
Section: Resultsmentioning
confidence: 99%
“…4. 67–71 Firstly, the cycloaddition reaction began with the O atom of epoxide being activated by the Lewis acidic In 3+ and Tm 3+ sites to form In/Tm-epoxide adducts, resulting in the instability of the ternary rings. Subsequently, the Br − ions released from the co-catalyst of n -Bu 4 NBr launched an affinity attack on the C atom with less steric hindrance to produce the main intermediates of alkylcarbonate anions, whose O − atoms served as a nucleophilic reagent to react with CO 2 in the pores, generating the carbonate ester as the secondary intermediate.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, various MOFs with excellent catalytic activity in the cycloaddition of CO 2 with epoxide have been successively reported. 40–54 Previous reports showed that the unsaturated metal sites of MOFs as active Lewis acid centers could play a vital role in facilitating the cycloaddition of CO 2 with epoxides. 36,44–46 Dai et al 45 reported a [Zn 2 (iso) 2 (bpy) 2 ] n MOF with open metal sites, which exhibits exceptionally high catalytic activity for the cycloaddition of CO 2 and propylene oxide.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Metal-organic frameworks (MOFs) made of metal ions (metal ion clusters) and bridging organic linkers have shown benefits in terms of their large surface area, high porosity, low density, controlled structure, and programmable pore size. [8][9][10][11][12] To date, MOFs have been extensively applied in catalysis, 13 gas storage, 14 proton conduction, 15 energy storage, 16 and so on, 17 but the assembly processes of MOFs are still undetermined due to numerous factors. [18][19][20][21] Typically, solvent molecules can behave as weakly coordinated ligands to impact the formation of MOFs, even though typically, solvent molecules are not near the crystal lattice and only affect crystal growth.…”
Section: Introductionmentioning
confidence: 99%